Simulation Of Internet Applications Over General Packet Radio Service - Izaruku, Zubeir (2002)
The General Packet Radio Service (GPRS) has been designed as an evolutionary step towards the migration from 2nd Generation Wireless Communication Systems to 3rd Generation Wireless Communication systems. The major challenges in GPRS are on its ability to offer lower access delay, better data throughput and radio resource utilization compared to the existing cellular networks. And also on how GPRS can be implemented on the existing cellular networks with little impact on the existing voice services. This thesis examines the performance of the GPRS Air Interface through simulation. A GPRS network simulator was developed in OPNET™. Performance is judged in terms of Access Delay, Throughput, Point-to-Point delay and Radio Resource utilization over GPRS Network. Some Internet services (e.g. WWW, E-mail and FTP), which are expected to be the most commonly used applications over GPRS are evaluated. The results show that for small number of users in a cell, the access delay in GPRS is small compared to that of GSM and does not depend very much on the number of radio resources allocated for GPRS Service.GPRS offers higher data throughput than that of traditional Circuit Switched GSM where the maximum data rate per a physical channel is 9.6 Kb/s. However, the data throughput in GPRS become much less than that of GSM under high traffic load. When eight physical channels on a TDMA frame are used for GPRS under good channel conditions, the theoretical data throughput for the GPRS according to ETSI, is supposed to be 171 Kb/s. But our simulation results show that it is very difficult to achieve this kind of throughput due to signaling, protocol overhead the dynamic nature of the wireless channel that changes its state from good to bad resulting into retransmissions thereby reducing the overall throughput. These results could be useful for Radio Network Planners in implementing GPRS on the existing cellular Networks.